Communication on "architecting portfolios of systems". Issue 4 (3rd May 2019) - Maier, Mark W.
Abstract: During the review process for the paper "Architecting Portfolios of Systems" in this issue one of the reviewers suggested that part of the reviewer‐author dialog be published because it clarified some issues beyond the paper itself and illustrated some different perspectives. This paper elaborates three major topics: The categorization of different types of collections of systems, the concept of requisite modeling in how we choose to model systems under development across a spectrum of rigor, and how to judge the success of research in systems engineering processes and methods.